Razones de actividad como estrategia empresarial para tomar decisiones en una empresa productora de muebles en el período 2017-2018. - Roman Cadena, Nicole Stefany (My University, 2020)
At present, thanks to globalization, the markets have achieved success internationally, which has led to a more competitive market, for this reason the analysis of financial indicators is a fundamental tool in different companies that exist in the market , because this analysis allows you to accurately assess your financial situation; providing relevant information regarding its economic environment, in order to make correct decisions, improve business strategies and achieve business objectives. Corporación Colineal Cia. Ltda is a company located in the production and sale of wooden furniture, under the control of the company's Superintendence, with a 43-year history in the market, thanks to its excellent customer service as well as its constant innovation In its products it has positioned itself as one of the most recognized furniture industries nationally and internationally, such success is due to the quality of the products and its eco-friendly business policies. Based on this, the present titling work intends to evaluate the business management, by analyzing the results of the reasons for the activity applied to the financial statements of the 2017-2018 period of Colineal Corporation Cia. Ltda, in order to know its importance in decision making, in order to obtain the financial information that is necessary to access the official website of the Superintendence of Companies, and detect the statements of financial situation of the 2018-2017 period and statements of results of the 2018-2017 period for their respective analysis, with the proposal to measure the methodology with which the company manages the resources available, said process was carried out through the use of the portfolio recovery ratio, average collection period, inventory turnover, inventory of finished products purchased from third parties, average age of inventories, average payment period, average operational cycle and turnover of total assets s, used as a business management strategy for correction and timely decision making. Given the aforementioned, the case was developed under the approach of quantitative and qualitative, quantitative modality because it is based on a series of mathematical operations based on the information presented by the Corporation Colineal Cia. Ltda in its financial statements and indicator formulas financial and qualitative to carry out an analysis and interpretation of the results shown in the calculation of activity indicators. In addition, in order to complement and make the research process more feasible, it was necessary to use three fundamental methodologies, first the non-experimental method, since the research does not seek to intentionally vary the variables, second, it is convenient to apply is the method deductive-inductive since it allows to pass from a general knowledge to a more specific one, and finally to argue the research process the documentary bibliographic research method will be applied. Finally, a research process has been carried out, where concepts related to the subject of research such as financial administration, administration activities, financial statements, financial indicators, activity indicators formula, among others, were also used. Interview technique with the purpose of knowing the accountant's judgment regarding the use of financial indicators, and confirming data from the periods mentioned above. Finally, the financial indicators were applied, so it was determined that the company for the 2017 period recovers its portfolio 9.43 times in relation to its credit sales, which compared to the result of the year 2018 that was 11 times, a minimal variation, but which is still considered favorable, since it recovers its portfolio 1.57 times faster and indicates that its strategies to convert its accounts receivable into cash have improved and that its customer credit study has been more selective to the Time to grant credits. On the other hand, in the 2018 period it takes 33.19 days to recover the accounts receivable, which compared to the 2017 period was 38.71, the number of days in which it recovers its sales on credit to decreased, which means that the entity improved its processes of charge, however, is considered unfavorable since it is not within the range of 30 days. It was also evident that Colineal Corporation Cia. Ltda in the 2018 period rotates its inventory 2.40 times, which compared to the previous 2017 period that was 2.16 times, a slight increase is evidenced, which is favorable since while The higher this indicator is considered better as it means that the merchandise is current and the management of its inventories is efficient. On the other hand, in the 2018 period the average age of its inventories of 152.21 days, which compared to the year 2017 that was 168.85 days, a decrease is evidenced which is favorable and has improved its sales levels so it rotates more often their inventories having a positive impact on liquidity in the company. Likewise, it is the 2018 period paid off its debts with suppliers every 124.48 days, which compared to the previous 2017 period was 127.12 days shows an improvement in the acceleration of payments with third parties, which is favorable since it allows it to demonstrate other entities that have the capacity to fulfill their obligations. The company Colineal Corporation Cia. Ltda in the 2018 period reflected an average of 92.70 days to convert its accounts receivable into cash and the inventories that compared to the result of the 2017 period that was 103.78 days it is evident that the indicator It has decreased 11.08 days, which is considered favorable since it makes its accounts receivable effective in less time. The company in the 2018 period rotates its assets 1.21 times, which compared to the year 2017 that was 1.08 times, it is evident that the result has increased what is considered favorable since as high as this indicators means that the management in the Use of your assets is efficient to generate income.
En la actualidad, gracias a la globalización los mercados han logrado conectarse a escala internacional, lo que ha provocado que se genere un mercado más competitivo, por esta razón el análisis de los indicadores financieros es una herramienta fundamental en diferentes empresas que existen en el mercado, pues dicho análisis permite evaluar con exactitud su situación financiera; aportando información relevante respecto a su entorno económico, con la finalidad de tomar decisiones correctas, mejorar las estrategias empresariales y llegara cumplir los objetivos empresariales. Colineal Corporation Cia. Ltda es una empresa dedicada a la producción y venta de muebles de madera, bajo el control de la Superintendencia de compañía, con una trayectoria de 43 años en el mercado, gracias a su excelente atención al cliente así como su constante innovación en sus productos los ha posicionado como una de las industrias de muebles más reconocida a nivel nacional e internacional, tal éxito se debe a la calidad en los productos y sus políticas empresariales amigables con el ecosistema. En función a ello, el presente trabajo de titulación pretende evaluar la gestión empresarial, mediante el análisis de los resultados de las razones de actividad aplicados a los estados financiero periodo 2017-2018 de Colineal Corporation Cia. Ltda, a fin de conocer su importancia en la toma de decisiones, para obtener la información financiera fue necesario acceder a la página oficial de la Superintendencia de Compañías, y extraer los estados de situación financiera del periodo 2018-2017 y estados de resultados del periodo 2018-2017 para su respectivo análisis, con la finalidad de medir efectividad con la que la empresa maneja los recursos que dispone, dicho proceso fue realizado mediante el uso de la razón de recuperación de cartera, periodo promedio de cobros, rotación de inventarios, inventario de productos terminados comprado a terceros, edad promedio de inventarios, periodo promedio de pago, ciclo operacional promedio y rotación de activos totales, usados como estrategia de gestión empresarial para la correcta y oportuna toma de decisiones. Ante lo mencionado anteriormente, el caso fue desarrollado bajo el enfoque de la modalidad cuantitativo y cualitativo, cuantitativo porque se basa en una serie de operaciones matemáticas en base a la información que presenta la Corporation Colineal Cia. Ltda en sus estados financieros y fórmulas de indicadores financieros y cualitativos para llevar a cabo un análisis e interpretación de los resultados arrojados en el cálculo los indicadores de actividad. Además, con la finalidad de complementar y hacer más factible el proceso de investigación, fue necesario emplear tres metodologías fundamentales, primero el método no experimental, puesto que la investigación no busca hacer variar intencionalmente las variables, segundo, es conveniente a aplicar es el método deductivo-inductivo ya que permite pasar de un conocimiento general a uno más específico, y por ultimo para argumentar el proceso de investigación se aplicara el método de investigación bibliográfica documental. Por último, se ha llevado a cabo un proceso de investigación, donde se exponen conceptos referente al tema de investigación como administración financiera, actividades de la administración, estados financieros, indicadores financieros, formula de indicadores de actividad, entre otros, además se usó la técnica de la entrevista con la finalidad de conocer el juicio del contador respecto al uso de indicadores financieros, y confirmar datos de los periodos ya antes mencionados. finalmente se procedió con la aplicación de los indicadores financieros, de tal manera se determinó que la empresa para el período 2017 recupera su cartera 9.43 veces en relación a sus ventas a crédito, que comparado con el resultado del año 2018 que fue de 11 veces, una variación mínima, pero que de todas maneras se considera favorable, puesto que recupera su cartera 1.57 veces más rápido e indican que sus estrategias de convertir en efectivo sus cuentas por cobrar han mejorado y que su estudio crediticio de clientes ha sido más selectivo a la hora de otorgar créditos. En cambio, en el período 2018 tarda 33.19 días en recuperar las cuentas por cobrar, que comparado con el período 2017 fue de 38.71, el número días en que recupera sus ventas a crédito a disminuido, lo que significa que la entidad mejoró sus procesos de cobro, sin embargo se considera desfavorable ya que no se encuentra dentro del rango de 30 días. Se evidenció también, que Colineal Corporation Cia. Ltda en el período 2018 rota su inventario 2,40 veces, que comparado con el periodo anterior 2017 que fue de 2,16 veces, se evidencia un leve incremento, lo cual es favorable ya que mientras más alto sea este indicador se considera mejor ya que significa la mercadería es actual y la gestión de sus inventarios es eficiente. Po otra parte, en el período 2018 la edad promedio de sus inventarios de 152,21 días, que comparado con el año 2017 que fue de 168.85 días se evidencia una disminución lo cual resulta favorable ya ha mejorado sus niveles de venta por lo cual rota más seguido sus inventarios repercutiendo positivamente en la liquidez en la empresa. Así mismo, es el período 2018 saldó sus deudas con proveedores cada 124,48 días, que comparado con el periodo anterior 2017 fue de 127.12 días muestra una mejora en la aceleración de pagos con terceros, lo cual es favorable puesto que le permite demostrar a otras entidades que tiene la capacidad de cumplir con sus obligaciones. La empresa Colineal Corporation Cia. Ltda en el período 2018 reflejó un promedio de 92,70 días para convertir en efectivo sus cuentas por cobrar y los inventarios que comparados con el resultado del periodo 2017 que fue de 103,78 días se evidencia que el indicador ha disminuido 11.08 días, lo cual se considera favorable puesto hace efectivos sus cuentas por cobrar en menos tiempo. La empresa en el período 2018 rota sus activos 1.21 veces, que en comparación al año 2017 que fue de 1.08 veces, se evidencia que el resultado ha incrementado lo que se considera favorable ya que mientras as alto sea este indicadores significa que la gestión en el uso de sus activos es eficiente para generar ingresos.
Keywords: ADMINISTRACIÓN FINANCIERA; ANÁLISIS; ESTADOS FINANCIEROS; INDICADORES